Plant tissue type and mineral contents shape endophytic bacterial communities in the Sisrè berry plant [Synsepalum dulcificum (Schumach & Thonn.) Daniell] in Benin - Rabiath F. R. Adigoun; Alexis Durand; Hervé N. S. Aholoukpè; Dèdéou A. Tchokponhoué; Enoch G. Achigan-Dako; Aimé H. Bokonon-Ganta; Emile Benizri (PLoS ONE, 2025)
Diverse endophytic bacteria inhabit distinct tissues of a given species and are essential for plant growth and resilience to various stresses. Little information is available on bacterial endophytes associated with Synsepalum dulcificum, an opportunity fruit crop with high economic and medicinal values. Using Illumina sequencing of the bacterial 16S rRNA gene, the diversity and structure of the endophytic bacterial community in the roots and leaves of S. dulcificum were determined, considering 29 accessions from three distinct phenotypes located either in home gardens or on farms in Benin. 2,468 Operational Taxonomic Units (OTUs) were recorded in the leaf and root endosphere of S. dulcificum, affiliated with 20 bacterial phyla, 49 classes, 125 orders, 217 families and 365 genera. Actinomycetota, Pseudomonadota and Chloroflexota were the most abundant phyla in the roots. In comparison, Pseudomonadota stood out as almost the unique phylum in the leaves, suggesting a significant decrease in diversity from roots to leaves. Significant correlations (p < 0.05) were observed between the relative abundance of the endophytic bacterial taxa and the mineral contents in the leaves, roots, and soil. While bacterial communities depended highly on accession, plant phenotype and habitat discriminated them in roots and leaves, respectively. Metagenome function prediction indicated that S. dulcificum harbors bacteria with the potential to metabolize carbohydrates and amino acids, as well as synthesize secondary metabolites and antimicrobial compounds beneficial for plant growth and adaptation to environmental stresses. These findings open room for exploiting endophytic diversity to enhance the growth and sustainable production of S. dulcificum.